Immune repertoire analysis of normal Chinese donors at different ages. Issue 11 (4th August 2022) - Song, Cailing; Pan, Wenjing; Brown, Brittany; Tang, Congli; Huang, Yunqi; Chen, Houao; Peng, Nan; Wang, Zhe; Weber, Daniel; Byrne‐Steele, Miranda; Wu, Haijing; Liu, Hongna; et al.
Abstract: Objectives: This study investigated the characteristics of the immune repertoire in normal Chinese individuals of different ages. Materials and Methods: In this study, all seven receptor chains from both B and T cells in peripheral blood of 16 normal Chinese individuals from two age groups were analyzed using high‐throughput sequencing and dimer‐avoided multiplex PCR amplification. Normal in this study is defined as no chronic, infectious or autoimmune disease within 6 months prior to blood draw. Results: We found that compared with the younger group, the clonal expression of T‐cell receptor repertoire increased in the older group, while diversity decreased. In addition, we found that the T‐cell receptor repertoire was more significantly affected by age than the B‐cell receptor repertoire, including significant differences in the use of the unique TCR‐alpha and TCR‐beta V‐J gene combinations, in the two groups of normal participants. We further analyzed the degree of complementarity determining region 3 sequence sharing between the two groups, and found shared TCR‐alpha, TCR‐gamma, immunoglobulin‐kappa and immunoglobulin‐lambda chain complementarity determining region 3 sequences in all subjects. Conclusion: Taken together, our study gives us a better understanding of the immune repertoire of different normal Chinese people, and these results can be applied to the treatment of age‐related diseases. Immune repertoire analysis also allows us to observe participant's wellness, aiding in early‐stage diagnosis. Abstract : With aging, the body's thymus involution, T and B cells senescence, T cell clones expand, the diversity of the TCR repertoire decreases, and the immunity of the body's immune system decreases.